2019
DOI: 10.3233/jad-180875
|View full text |Cite
|
Sign up to set email alerts
|

Altered Neural Networks in the Papez Circuit: Implications for Cognitive Dysfunction after Cerebral Ischemia

Abstract: Cerebral ischemia remains a leading cause of mortality worldwide. Although the incidence of death has decreased over the years, surviving patients may suffer from long-term cognitive impairments and have an increased risk for dementia. Unfortunately, research aimed toward developing therapies that can improve cognitive outcomes following cerebral ischemia has proved difficult given the fact that little is known about the underlying processes involved. Nevertheless, mechanisms that disrupt neural network activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 198 publications
(185 reference statements)
1
22
0
Order By: Relevance
“…As a result of ischemia, the blood supply to neurons is interrupted, which then promotes a series of pathophysiological responses. Various pathological changes are involved individually or jointly in the ischemic process, including autophagy, apoptosis, inflammation, excitatory toxicity, mitochondrial death pathways and free radical release (Khoshnam et al, 2017;Sekerdag et al, 2018), all of which lead to neuronal cell death, hindering important motor (Sun et al, 2012), sensory (Graf et al, 1986) and cognitive functions (Escobar et al, 2019;. Ischemic stroke has been considered one of the main factors that cause aging of the brain and the pathological state of neurodegenerative diseases (Sommer, 2017;Graham and Liu, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…As a result of ischemia, the blood supply to neurons is interrupted, which then promotes a series of pathophysiological responses. Various pathological changes are involved individually or jointly in the ischemic process, including autophagy, apoptosis, inflammation, excitatory toxicity, mitochondrial death pathways and free radical release (Khoshnam et al, 2017;Sekerdag et al, 2018), all of which lead to neuronal cell death, hindering important motor (Sun et al, 2012), sensory (Graf et al, 1986) and cognitive functions (Escobar et al, 2019;. Ischemic stroke has been considered one of the main factors that cause aging of the brain and the pathological state of neurodegenerative diseases (Sommer, 2017;Graham and Liu, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is growing evidence that cerebrovascular disease leads to dysfunction of the Papez circuit. Escobar et al reported that cerebral ischemia patients exhibited abnormal structural and functional connections in the Papez circuit, which were closely related to cognitive function (41). Furthermore, structural and functional abnormalities in the HIP were observed in cerebrovascular disease patients (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Switching to alternative neuronal connection is the way to overcome this loss, which depends upon the plasticity of the brain [8]. The consistent failure of neuronal connections is responsible for daily fluctuations in behavior, and they are interconnected with the accumulation of plaques and tangles, which in turn cause neuronal loss and network dysfunction [9,10].…”
Section: Neurodegeneration and Tauopathiesmentioning
confidence: 99%